Greenland, view of junction of Kejser Franz Joseph and Kjerulf Fjords - Boyd, Louise Arner, 1887-1972 (1931)
Entrance to Gregory Valley from junction of Franz Josef [Kejser Franz Joseph] & Kjerulfs [Kjerulf] Fjord.